High performance nitrogen-containing cemented carbide material based on vanadium-titanium carbonitride solid solution and preparation method thereof

By modifying the tungsten carbide of cemented carbide materials and introducing vanadium titanium carbon nitride solid solution and boron quantum dot modified high-entropy alloy, the hardness and fracture strength of cemented carbide materials are solved. Problem, the performance improvement and application scope of cemented carbide materials have been achieved.

CN119242977BActive Publication Date: 2025-02-25CHENGDU BANGPU CUTTING TOOLS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411770747.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-25
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

When cutting difficult-to-process materials, existing cemented carbide materials have low Rockwell hardness, low lateral fracture strength, and large phase particle size, which limits their range in cutting tool applications.

Method used

By modifying the hard phase tungsten carbide and introducing a vanadium titanium carbon nitride solid solution and boron quantum dot modified high entropy alloy, the hardness of the cemented carbide material is improved through the interaction between the modified components and Transverse fracture strength while reducing phase particle size.

Benefits of technology

The Rockwell hardness and lateral fracture strength of cemented carbide materials are significantly improved, reducing phase particle size, thus extending its range in cutting tool applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution and a preparation method thereof, and belongs to the technical field of cemented carbide cutting tool materials. The present invention modifies tungsten carbide of a hard phase, and simultaneously introduces a vanadium-titanium carbonitride solid solution and a boron quantum dot modified high entropy alloy, and through the interaction between the modified components, effectively improves the hardness and transverse fracture strength of the cemented carbide material, while reducing the phase particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cemented carbide cutting tool materials, and in particular relates to a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution and a preparation method thereof. Background Art

[0002] Cemented carbide is a metal-based composite material made of refractory metal carbide as the hard phase and metal as the bonding phase by powder metallurgy, also known as cermet; the hard phase has the advantages of high hardness, high wear resistance, high melting point and high thermal stability, while the tough metal bonding phase provides good ductility, toughness and excellent wettability. Cemented carbide has the comprehensive advantages of both the hard phase and the bonding phase, with high strength, hardness, wear resistance, high elastic modulus, low thermal expansion coefficient and good fracture toughness. At present, cemented carbide has been widely used in mining drilling tools, machining tools, mold manufacturing, mining excavation, national defense and military industries.

[0003] A Chinese patent (publication number CN109811235B) discloses a highly wear-resistant cemented carbide and its preparation method. The invention uses a composite powder composed of TiC-Ni-based spherical particles and WC-Co-based powder as raw materials, and adopts a low-temperature pressure holding method to prepare the cemented carbide. The prepared cemented carbide has the advantages of both wear resistance and toughness. The low-temperature pressure holding method can achieve full densification inside the alloy and effectively control the growth of grains during the sintering process, thereby improving the strength and wear resistance of the cemented carbide. However, the patented technology has not solved the problems of low Rockwell hardness, low transverse fracture strength, and large phase particle size of existing cemented carbide materials. When cemented carbide materials are used in the cutting of difficult-to-process materials, such as titanium alloy cutting, intermetallic compound cutting, high-temperature alloy cutting, etc., the above problems will limit their use.

[0004] Therefore, how to select suitable hard phase materials and cooperate with multiple binding phases to improve the hardness and transverse fracture strength of cemented carbide materials, while reducing the phase particle size, thereby expanding the application range of cutting tools prepared using the cemented carbide materials, has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution and a preparation method thereof, aiming to solve the problems of low Rockwell hardness, low transverse rupture strength, and large material phase particle size when the existing cemented carbide materials are used for cutting difficult-to-cut materials.

[0006] The present invention modifies the hard phase tungsten carbide and introduces vanadium titanium carbonitride solid solution and boron quantum dots to modify the high entropy alloy. Through the interaction between the modified components, the hardness and transverse fracture strength of the cemented carbide material are effectively improved, while the phase particle size is reduced, thereby expanding the application range of the cutting tool prepared using the cemented carbide material.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] The first aspect of the present invention provides a method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution, comprising the following steps:

[0009] Step S1: by weight, 70-90 parts of tungsten carbide, 20-25 parts of vanadium titanium carbonitride solid solution and 10-15 parts of high entropy alloy are mixed evenly and wet ball milled, and then dried after the ball milling is completed, and then 1-3 parts of a molding agent are added, sieved, granulated, and a granular mixture is obtained;

[0010] Step S2: loading the granular mixture described in step S1 into the cavity of the mold and pressing it into a cemented carbide blank;

[0011] Step S3: placing the cemented carbide blank described in step S2 in a low-pressure sintering furnace, evacuating to 0.1 Pa, debinding at 400-550°C for 1-2 hours, then heating to 1150-1200°C for sintering for 1-2 hours, and then heating to 1420-1450°C for a first insulation for 1.5-2.5 hours. After the first insulation is completed, argon gas is introduced for a second insulation for 0.5-0.8 hours, and finally cooled to room temperature with the furnace to obtain a high-performance nitrogen-containing cemented carbide material based on vanadium-titanium carbonitride solid solution.

[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0013] As a preferred technical solution of the present invention, the tungsten carbide is modified tungsten carbide; the preparation method of the modified tungsten carbide comprises: adding 140-150 parts of ammonium metatungstate, 10-12 parts of erbium nitrate and 8-10 parts of gadolinium nitrate to 300-400 parts of deionized water by weight, stirring for 20-30 minutes, then adding 20-25 parts of glucose, stirring for 1-2 hours and then standing for 20-24 hours to obtain a mixed liquid; spray drying and crystallization treatment of the mixed liquid to obtain a mixed precursor; first placing the mixed precursor in an argon atmosphere, calcining at 460-480°C for 30-40 minutes, and then placing it in a hydrogen atmosphere, calcining at 900-950°C for 50-60 minutes to obtain modified tungsten carbide.

[0014] Preferably, the conditions for the spray drying crystallization treatment include: the inlet air temperature of the spray drying tower is 200-220°C, the outlet air temperature is 90-95°C, the feed rate is 120-150 mL / min, and the spray pressure is 1.2-1.5 MPa.

[0015] Doping erbium into modified tungsten carbide can hinder the migration of tungsten carbide grain boundaries, thereby inhibiting the growth of tungsten carbide grains, and can even out the grain size, reduce the number of pores and abnormally grown tungsten carbide grains, thereby reducing the particle size of tungsten carbide phase in cemented carbide materials; while the introduction of gadolinium promotes the refinement of tungsten carbide grains, making the microstructure of cemented carbide materials more uniform. At the same time, gadolinium has a strong affinity with nitrogen and carbon elements in the solid solution, and can form stable compounds, increase the wettability of tungsten carbide and other interfaces, and synergistically improve the hardness of the material.

[0016] As a preferred technical solution of the present invention, the preparation method of the vanadium titanium carbonitride solid solution comprises: adding 6 to 8 parts of 2-methylimidazole to 80 to 90 parts of methanol by weight, stirring for 20 to 30 minutes to obtain liquid A; adding 3 to 5 parts of tetrabutyl titanate and 0.5 to 0.8 parts of ferric acetylacetonate to 40 to 50 parts of methanol, stirring for 20 to 30 minutes to obtain liquid B; mixing 80 to 90 parts of liquid A and 40 to 50 parts of liquid B, stirring for 24 to 30 hours at room temperature, and then filtering to obtain a filter residue. The filter residue is washed and dried, and then placed in a nitrogen atmosphere and treated at 1000~1050°C for 1~2 hours to obtain titanium-doped carbonitride; 40~60 parts of titanium-doped carbonitride and 10~15 parts of vanadium-containing MXene are added to 100~120 parts of N,N-dimethylformamide, and ultrasonically treated for 2~4 hours. After the treatment, the solid is filtered to obtain the solid, and the solid is washed and dried, and then placed in a nitrogen atmosphere and treated at 380~400°C for 1~2 hours to obtain a vanadium-titanium carbonitride solid solution.

[0017] As a preferred technical solution of the present invention, the preparation method of the vanadium-containing MXene includes: adding 1 to 3 parts of lithium fluoride to 10 to 15 parts of a hydrochloric acid solution with a molar concentration of 1 mol / L, stirring for 50 to 60 minutes, and then adding 1 to 3 parts of vanadium aluminum carbide and stirring for 35 to 45 minutes to obtain a mixed solution; stirring the mixed solution at 125 to 130° C. for 50 to 60 hours, washing with deionized water and anhydrous ethanol in turn, centrifuging, and vacuum drying to obtain the vanadium-containing MXene.

[0018] The vanadium-titanium carbonitride solid solution can slow down the dissolution and recrystallization rate of tungsten carbide and inhibit the growth of tungsten carbide grains. At the same time, the solid solution will segregate at the interface of tungsten carbide / entropy alloy, hindering the migration of tungsten carbide interface, preventing the aggregation and growth of tungsten carbide particles, and effectively reducing the particle size of tungsten carbide phase; vanadium, titanium and other elements in the solid solution can form complexes with the hard phase, segregate around the grains, inhibit crack growth and change the crack propagation path, thereby improving the transverse fracture strength of cemented carbide materials.

[0019] As a preferred technical solution of the present invention, the high entropy alloy is a boron quantum dot modified high entropy alloy; the preparation method of the boron quantum dot modified high entropy alloy comprises: adding 2 to 4 parts of ammonium chlororuthenate, 2 to 4 parts of nickel chloride, 2 to 4 parts of ferric chloride, 2 to 4 parts of samarium nitrate and 2 to 4 parts of neodymium nitrate to 100 to 150 parts of deionized water by weight, stirring for 1 to 2 hours, then adding 10 to 15 parts of ammonium chloride, ultrasonically stirring for 2 to 4 hours at 80 to 85°C, freeze-drying to obtain a high entropy alloy precursor; mixing 10 to 20 parts of the high entropy alloy precursor and 3 to 6 parts of boron quantum dots evenly, and then ball milling at a speed of 800 to 1000 r / min for 1 to 2 hours to obtain mixed nanoparticles; calcining the mixed nanoparticles at 280 to 300°C for 2 to 4 hours, and then treating at 560 to 600°C for 2 to 4 hours to obtain a boron quantum dot modified high entropy alloy.

[0020] As a preferred technical solution of the present invention, the preparation method of boron quantum dots includes: adding 2 to 4 parts of ammonium pentaborate and 1 to 2 parts of boric acid to 20 to 25 parts of deionized water by weight, stirring for 1 to 2 hours, placing in an argon atmosphere for hydrothermal reaction, cooling to room temperature after the reaction, adding 1 to 2 parts of hydrazine hydrate and stirring for 1 to 2 hours, and then centrifuging to obtain a supernatant, and freeze-drying the supernatant to obtain boron quantum dots.

[0021] Preferably, the reaction temperature of the hydrothermal reaction is 180-185° C., and the reaction time is 10-12 h.

[0022] Boron quantum dots in high entropy alloys modified with boron quantum dots have good affinity with nitrogen in the solid solution and can form stable covalent bonds through hybrid orbitals. Boron and nitrogen can improve the interface bonding state between the hard phase and other phases through the action of covalent bonds, reduce interface defects, and improve the transverse fracture strength of cemented carbide materials. Ruthenium in high entropy alloys is dispersed in tungsten carbide grains and grain boundaries, which has a dispersion strengthening effect on the alloy; samarium can promote the refinement of grains in cemented carbide, which increases the grain boundary area and improves the material's deformation resistance; neodymium strengthens the grain's resistance to dislocation deformation and improves the toughness of cemented carbide. The combined effect improves the hardness of cemented carbide materials.

[0023] Preferably, the molding agent is selected from any one of paraffin, polyethylene glycol, and polyvinyl alcohol, or a combination of at least two thereof.

[0024] The second aspect of the present invention provides a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution prepared by the method described in the first aspect.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention introduces gadolinium into the hard phase to form a stable compound with nitrogen and carbon elements in the solid solution, thereby increasing the wettability of tungsten carbide and other interfaces; in addition, ruthenium, samarium and neodymium elements in the high entropy alloy are used in combination to jointly improve the Rockwell hardness of the cemented carbide material, ensuring that it has sufficient hardness when used as a cutting tool.

[0027] (2) The present invention forms a complex between vanadium, titanium and other elements in the solid solution and the hard phase to inhibit crack growth and change the crack propagation path; the boron quantum dots in the boron quantum dot modified high entropy alloy have good affinity with the nitrogen element in the solid solution and can form stable covalent bonds through hybrid orbitals, thereby improving the interface bonding state between the hard phase and other phases, synergistically improving the transverse fracture strength of the cemented carbide material and ensuring its service life when used as a cutting tool.

[0028] (3) The present invention inhibits the migration of tungsten carbide grain boundaries by doping erbium elements into the modified tungsten carbide, thereby inhibiting the growth of tungsten carbide grains and reducing the number of pores and abnormally grown tungsten carbide grains; the vanadium-titanium carbonitride solid solution can slow down the dissolution and recrystallization rate of tungsten carbide and inhibit the growth of tungsten carbide grains, thereby synergistically reducing the particle size of the tungsten carbide phase in the cemented carbide material. DETAILED DESCRIPTION

[0029] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0030] The sources of some components in the embodiments and comparative examples are as follows:

[0031] Ammonium metatungstate, CAS No. 14311-52-5, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0032] Erbium nitrate, CAS No. 10031-51-3, was purchased from Adamas Beta (Shanghai) Chemical Reagent Co., Ltd.;

[0033] Gadolinium nitrate, CAS No. 19598-90-4, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0034] Glucose, CAS number 34620-77-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0035] Lithium fluoride, CAS No. 7789-24-4, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0036] Hydrochloric acid, CAS No. 7647-01-0, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0037] Vanadium aluminum carbide, product number 2309004, purchased from Forsman Technology (Beijing) Co., Ltd.;

[0038] 2-Methylimidazole, CAS No. 693-98-1, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0039] Methanol, CAS number 67-56-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0040] Tetrabutyl titanate, product number PA86584, purchased from Shanghai Chuangsai Technology Co., Ltd.;

[0041] Ferric acetylacetonate, catalog number PA54345, was purchased from Shanghai Chuangsai Technology Co., Ltd.;

[0042] N,N-dimethylformamide (DMF), CAS number 68-12-2, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0043] Ammonium pentaborate, CAS No. 12007-89-5, purchased from Merck Chemical Co., Ltd.;

[0044] Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0045] Hydrazine hydrate, CAS No. 7803-57-8, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;

[0046] Ammonium chlororuthenate, CAS No. 18746-63-9, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0047] Nickel chloride, CAS No. 7718-54-9, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0048] Ferric chloride, CAS No. 7705-08-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0049] Samarium nitrate, CAS No. 10361-83-8, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0050] Neodymium nitrate, CAS No. 14517-29-4, purchased from Zibo Ruibokang Rare Earth Materials Co., Ltd.;

[0051] Ammonium chloride, CAS No. 12125-02-9, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0052] Paraffin wax, catalog number PA73266, purchased from Shanghai Chuangsai Technology Co., Ltd.;

[0053] Polyethylene glycol, catalog number S30184, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0054] Polyvinyl alcohol, product number F-041238, was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;

[0055] Commercially available tungsten carbide, CAS number 12070-13-2, was purchased from Xiamen Jinlu Special Alloy Co., Ltd.;

[0056] Cobalt powder, CAS No. 7440-48-4, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0057] Commercially available high entropy alloy, FeCrNiMnAl, with a size of 15-53 μm, was purchased from Beijing Zhongke Yannuo New Materials Co., Ltd.

[0058] Preparation of modified tungsten carbide: In parts by weight, 150 parts of ammonium metatungstate, 12 parts of erbium nitrate and 10 parts of gadolinium nitrate are added to 400 parts of deionized water, stirred for 30 minutes, and then 25 parts of glucose are added. After stirring for 2 hours, the mixture is allowed to stand for 24 hours to obtain a mixed liquid; the mixed liquid is spray-dried and crystallized (the inlet temperature of the spray drying tower is 220°C, the outlet temperature is 95°C, the feed amount is 150mL / min, and the spray pressure is 1.5MPa) to obtain a mixed precursor; the mixed precursor is first placed in an argon atmosphere, calcined at 480°C for 30 minutes, and then placed in a hydrogen atmosphere, calcined at 950°C for 60 minutes to obtain modified tungsten carbide.

[0059] Preparation of vanadium titanium carbonitride solid solution: (1) Add 3 parts of lithium fluoride to 15 parts of 1 mol / L hydrochloric acid solution by weight, stir for 60 minutes, then add 3 parts of vanadium aluminum carbide and stir for 45 minutes to obtain a mixed solution; stir the mixed solution at 130°C for 60 hours, wash with deionized water and anhydrous ethanol in turn, centrifuge and vacuum dry to obtain vanadium-containing MXene. (2) In parts by weight, 8 parts of 2-methylimidazole were added to 90 parts of methanol and stirred for 30 minutes to obtain liquid A; 5 parts of tetrabutyl titanate and 0.8 parts of ferric acetylacetonate were added to 50 parts of methanol and stirred for 30 minutes to obtain liquid B; 90 parts of liquid A and 50 parts of liquid B were mixed, stirred at room temperature for 24 hours, and then filtered to obtain a filter residue, which was washed and dried, and then placed in a nitrogen atmosphere and treated at 1050°C for 1 hour to obtain titanium-doped carbonitride; 60 parts of titanium-doped carbonitride and 15 parts of vanadium-containing MXene were added to 120 parts of N,N-dimethylformamide and ultrasonically treated for 4 hours. After the treatment, the solid was filtered to obtain a solid, which was washed and dried, and then placed in a nitrogen atmosphere and treated at 400°C for 2 hours to obtain a vanadium-titanium carbonitride solid solution.

[0060] Preparation of boron quantum dot modified high entropy alloy: (1) In parts by weight, 4 parts of ammonium pentaborate and 2 parts of boric acid are added to 25 parts of deionized water and stirred for 2 hours. The mixture is placed in an argon atmosphere for hydrothermal reaction (reaction temperature is 185°C, reaction time is 10 hours). After the reaction is completed, the mixture is cooled to room temperature, 2 parts of hydrazine hydrate are added and stirred for 2 hours, and then centrifuged to obtain a supernatant. The supernatant is freeze-dried to obtain boron quantum dots. (2) In parts by weight, 4 parts of ammonium chlororuthenate, 4 parts of nickel chloride, 2 parts of ferric chloride, 2 parts of samarium nitrate and 3 parts of neodymium nitrate were added to 100 parts of deionized water, stirred for 2 hours, and then 10 parts of ammonium chloride were added. The mixture was ultrasonically stirred at 85°C for 2 hours, and freeze-dried to obtain a high entropy alloy precursor; 15 parts of the high entropy alloy precursor and 5 parts of boron quantum dots were mixed evenly, and then ball milled at a speed of 1000 r / min for 1 hour to obtain mixed nanoparticles; the mixed nanoparticles were first calcined at 300°C for 2 hours, and then treated at 600°C for 2 hours to obtain a boron quantum dot modified high entropy alloy.

[0061] Example 1

[0062] This embodiment provides a method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution, comprising the following steps:

[0063] Step S1: in parts by weight, 90 parts of modified tungsten carbide, 25 parts of vanadium titanium carbonitride solid solution and 15 parts of boron quantum dot modified high entropy alloy are mixed evenly and wet ball milled, and then dried after the ball milling is completed, and then 3 parts of paraffin are added, sieved, granulated, and a granular mixture is obtained;

[0064] Step S2: loading the granular mixture described in step S1 into the cavity of the mold and pressing it into a cemented carbide blank;

[0065] Step S3: placing the cemented carbide blank described in step S2 in a low-pressure sintering furnace, evacuating to 0.1 Pa, debinding at 550°C for 1 hour, then heating to 1200°C for sintering for 1 hour, and then heating to 1450°C for a first insulation for 1.5 hours. After the first insulation is completed, argon gas is introduced for a second insulation for 0.5 hour, and finally cooled to room temperature with the furnace to obtain a high-performance nitrogen-containing cemented carbide material based on vanadium-titanium carbonitride solid solution.

[0066] Example 2

[0067] This embodiment provides a method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution, comprising the following steps:

[0068] Step S1: by weight, 70 parts of modified tungsten carbide, 20 parts of vanadium titanium carbonitride solid solution and 10 parts of boron quantum dot modified high entropy alloy are mixed evenly and wet ball milled, and then dried after the ball milling is completed, and then 1 part of polyethylene glycol is added, sieved, granulated, and a granular mixture is obtained;

[0069] Step S2: loading the granular mixture described in step S1 into the cavity of the mold and pressing it into a cemented carbide blank;

[0070] Step S3: placing the cemented carbide blank described in step S2 in a low-pressure sintering furnace, evacuating to 0.1 Pa, debinding at 400°C for 2 hours, then heating to 1150°C for sintering for 2 hours, and then heating to 1420°C for a heat preservation for 2.5 hours. After the first heat preservation is completed, argon gas is introduced for a second heat preservation of 0.8 hours, and finally cooled to room temperature with the furnace to obtain a high-performance nitrogen-containing cemented carbide material based on vanadium-titanium carbonitride solid solution.

[0071] Example 3

[0072] This embodiment provides a method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution, comprising the following steps:

[0073] Step S1: 80 parts by weight of modified tungsten carbide, 22 parts of vanadium titanium carbonitride solid solution and 14 parts of boron quantum dot modified high entropy alloy are mixed evenly and wet ball milled. After the ball milling is completed, the mixture is dried, and then 2 parts of polyvinyl alcohol are added, sieved, and granulated to obtain a granular mixture;

[0074] Step S2: loading the granular mixture described in step S1 into the cavity of the mold and pressing it into a cemented carbide blank;

[0075] Step S3: placing the cemented carbide blank described in step S2 in a low-pressure sintering furnace, evacuating to 0.1 Pa, debinding at 480°C for 2 hours, then heating to 1180°C for sintering for 1 hour, and then heating to 1440°C for a second heat preservation for 2 hours. After the first heat preservation is completed, argon gas is introduced for a second heat preservation of 0.6 hours, and finally cooled to room temperature with the furnace to obtain a high-performance nitrogen-containing cemented carbide material based on vanadium-titanium carbonitride solid solution.

[0076] Comparative Example 1

[0077] This comparative example provides a method for preparing a cemented carbide material. The difference from Example 1 is that this comparative example uses commercially available tungsten carbide instead of modified tungsten carbide, uses cobalt powder instead of vanadium titanium carbonitride solid solution, and uses commercially available high entropy alloy instead of boron quantum dot modified high entropy alloy. The rest is the same as Example 1.

[0078] Comparative Example 2

[0079] This comparative example provides a method for preparing a cemented carbide material. The difference from Example 1 is that this comparative example uses cobalt powder instead of vanadium titanium carbonitride solid solution, and uses commercially available high entropy alloy instead of boron quantum dot modified high entropy alloy, and the rest is the same as Example 1.

[0080] Comparative Example 3

[0081] This comparative example provides a method for preparing a cemented carbide material. The difference from Example 1 is that this comparative example uses commercially available tungsten carbide instead of modified tungsten carbide, and uses commercially available high entropy alloy instead of boron quantum dot modified high entropy alloy, and the rest is the same as Example 1.

[0082] Comparative Example 4

[0083] This comparative example provides a method for preparing a cemented carbide material. The difference from Example 1 is that this comparative example uses commercially available tungsten carbide instead of modified tungsten carbide, and uses cobalt powder instead of vanadium titanium carbonitride solid solution. The rest is the same as Example 1.

[0084] Comparative Example 5

[0085] This comparative example provides a method for preparing a cemented carbide material. The difference from Example 1 is that this comparative example uses commercially available tungsten carbide instead of modified tungsten carbide, and the rest is the same as Example 1.

[0086] Comparative Example 6

[0087] This comparative example provides a method for preparing a cemented carbide material. The difference from Example 1 is that cobalt powder is used in this comparative example to replace the vanadium-titanium carbonitride solid solution, and the rest is the same as Example 1.

[0088] Comparative Example 7

[0089] This comparative example provides a method for preparing a cemented carbide material. The difference from Example 1 is that this comparative example uses a commercially available high entropy alloy instead of the boron quantum dot-modified high entropy alloy, and the rest is the same as Example 1.

[0090] The performance of the cemented carbide materials provided in the above embodiments and comparative examples was tested, and the specific testing method is as follows:

[0091] (1) Rockwell hardness test

[0092] The Rockwell hardness is tested according to the requirements of GB / T 3849.1-2015 Cemented Carbide Rockwell Hardness Test (Scale A) Part 1: Test Method.

[0093] (2) Transverse rupture strength test

[0094] The transverse rupture strength is tested according to the requirements of GB / T 3851-2015 Method for Determination of Transverse Rupture Strength of Cemented Carbide.

[0095] (3) α (WC) phase particle size test

[0096] The α (WC) phase grain size is tested according to the requirements of GB / T 3488.2-2018 Metallographic determination of cemented carbide microstructure Part 2: Measurement of WC grain size.

[0097] The above performance test data is shown in Table 1.

[0098] Table 1 Performance test results

[0099] Rockwell hardness (HRA) Transverse rupture strength (MPa) α (WC) phase grain size (μm) Example 1 93.6 4460 0.57 Example 2 93.1 4452 0.59 Example 3 93.3 4455 0.58 Comparative Example 1 82.1 4016 0.81 Comparative Example 2 85.7 4019 0.72 Comparative Example 3 82.4 4178 0.71 Comparative Example 4 85.9 4182 0.79 Comparative Example 5 86.2 4436 0.68 Comparative Example 6 92.7 4195 0.67 Comparative Example 7 86.5 4199 0.59

[0100] From the above content, it can be seen that the present invention modifies the hard phase tungsten carbide, introduces vanadium titanium carbonitride solid solution and boron quantum dots to modify the high entropy alloy, and obtains high-performance nitrogen-containing cemented carbide materials based on vanadium titanium carbonitride solid solution (Examples 1 to 3) through the interaction between the modified components. The Rockwell hardness of the cemented carbide material is 93.1~93.6HRA, the transverse rupture strength is 4452~4460MPa, and the α (WC) phase particle size is 0.57~0.59μm.

[0101] The comparative example is significantly inferior to the embodiment in the corresponding performance test because it does not adopt the necessary technical solutions. Compared with Example 1, commercially available tungsten carbide is used to replace the modified tungsten carbide, cobalt powder is used to replace the vanadium titanium carbonitride solid solution, and the commercially available high entropy alloy is used to replace the boron quantum dot modified high entropy alloy, then the Rockwell hardness decreases, the transverse rupture strength decreases, and the α (WC) phase particle size increases (Comparative Example 1); Compared with Example 1, cobalt powder is used to replace the vanadium titanium carbonitride solid solution, and the commercially available high entropy alloy is used to replace the boron quantum dot modified high entropy alloy, then the Rockwell hardness decreases, the transverse rupture strength decreases, and the α (WC) phase particle size increases (Comparative Example 2); Compared with Example 1, commercially available tungsten carbide is used to replace the modified tungsten carbide, and the commercially available high entropy alloy is used to replace the boron quantum dot modified high entropy alloy, then the Rockwell hardness decreases, the transverse rupture strength decreases, and the α (WC) phase particle size increases. C) phase particle size increases (Comparative Example 3); Compared with Example 1, commercially available tungsten carbide is used instead of modified tungsten carbide, and cobalt powder is used instead of vanadium titanium carbonitride solid solution, then the Rockwell hardness decreases, the transverse rupture strength decreases, and the α (WC) phase particle size increases (Comparative Example 4); Compared with Example 1, commercially available tungsten carbide is used instead of modified tungsten carbide, then the Rockwell hardness decreases, and the α (WC) phase particle size increases (Comparative Example 5); Compared with Example 1, cobalt powder is used instead of vanadium titanium carbonitride solid solution, then the transverse rupture strength decreases, and the α (WC) phase particle size increases (Comparative Example 6); Compared with Example 1, a commercially available high entropy alloy is used instead of a boron quantum dot modified high entropy alloy, then the Rockwell hardness decreases, and the transverse rupture strength decreases (Comparative Example 7).

[0102] In summary, the present invention modifies the hard phase tungsten carbide and introduces vanadium titanium carbonitride solid solution and boron quantum dots to modify the high entropy alloy. Through the interaction between the modified components, the hardness and transverse fracture strength of the cemented carbide material are effectively improved, while the α (WC) phase particle size is reduced.

[0103] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution, characterized in that: The following steps are involved: Step S1: by weight, 70-90 parts of tungsten carbide, 20-25 parts of vanadium titanium carbonitride solid solution and 10-15 parts of high entropy alloy are mixed evenly and wet ball milled, and then dried after the ball milling is completed, and then 1-3 parts of a molding agent are added, sieved, granulated, and a granular mixture is obtained; Step S2: loading the granular mixture described in step S1 into the cavity of the mold and pressing it into a cemented carbide blank; Step S3: placing the cemented carbide blank described in step S2 in a low-pressure sintering furnace, evacuating to 0.1 Pa, debinding at 400-550° C. for 1-2 hours, then heating to 1150-1200° C. for sintering for 1-2 hours, and then heating to 1420-1450° C. for a first heat preservation of 1.5-2.5 hours. After the first heat preservation is completed, argon gas is introduced for a second heat preservation of 0.5-0.8 hours, and finally cooled to room temperature with the furnace to obtain a high-performance nitrogen-containing cemented carbide material based on vanadium-titanium carbonitride solid solution; The tungsten carbide is modified tungsten carbide; The preparation method of the modified tungsten carbide comprises: adding 140-150 parts of ammonium metatungstate, 10-12 parts of erbium nitrate and 8-10 parts of gadolinium nitrate to 300-400 parts of deionized water by weight, stirring for 20-30 minutes, then adding 20-25 parts of glucose, stirring for 1-2 hours and then standing for 20-24 hours to obtain a mixed liquid; spray drying and crystallization treatment of the mixed liquid to obtain a mixed precursor; placing the mixed precursor in an argon atmosphere, calcining at 460-480° C. for 30-40 minutes, and then placing it in a hydrogen atmosphere, calcining at 900-950° C. for 50-60 minutes to obtain modified tungsten carbide; The preparation method of the vanadium titanium carbonitride solid solution comprises: adding 6 to 8 parts of 2-methylimidazole to 80 to 90 parts of methanol by weight, stirring for 20 to 30 minutes to obtain liquid A; adding 3 to 5 parts of tetrabutyl titanate and 0.5 to 0.8 parts of ferric acetylacetonate to 40 to 50 parts of methanol, stirring for 20 to 30 minutes to obtain liquid B; mixing 80 to 90 parts of liquid A and 40 to 50 parts of liquid B, stirring for 24 to 30 hours at room temperature, and then filtering to obtain filter residue, washing the filter residue, and drying The obtained product is dried, placed in a nitrogen atmosphere, and treated at 1000-1050°C for 1-2 hours to obtain a titanium-doped carbonitride; 40-60 parts of the titanium-doped carbonitride and 10-15 parts of the vanadium-containing MXene are added to 100-120 parts of N,N-dimethylformamide, and ultrasonically treated for 2-4 hours. After the treatment, the solid is filtered to obtain a solid, which is washed and dried, and then placed in a nitrogen atmosphere and treated at 380-400°C for 1-2 hours to obtain a vanadium-titanium carbonitride solid solution; The high entropy alloy is a boron quantum dot modified high entropy alloy; the preparation method of the boron quantum dot modified high entropy alloy comprises: adding 2 to 4 parts of ammonium chlororuthenate, 2 to 4 parts of nickel chloride, 2 to 4 parts of ferric chloride, 2 to 4 parts of samarium nitrate and 2 to 4 parts of neodymium nitrate to 100 to 150 parts of deionized water by weight, stirring for 1 to 2 hours, then adding 10 to 15 parts of ammonium chloride, ultrasonically stirring for 2 to 4 hours at 80 to 85° C., freeze-drying to obtain a high entropy alloy precursor; uniformly mixing 10 to 20 parts of the high entropy alloy precursor and 3 to 6 parts of boron quantum dots, then ball milling for 1 to 2 hours at a speed of 800 to 1000 r / min to obtain mixed nanoparticles; first calcining the mixed nanoparticles at 280 to 300° C. for 2 to 4 hours, and then treating at 560 to 600° C. for 2 to 4 hours to obtain a boron quantum dot modified high entropy alloy.

2. The method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution according to claim 1, characterized in that: The conditions of the spray drying crystallization treatment include: the inlet air temperature of the spray drying tower is 200-220° C., the outlet air temperature is 90-95° C., the feed rate is 120-150 mL / min, and the spray pressure is 1.2-1.5 MPa.

3. The method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution according to claim 1, characterized in that: The preparation method of the vanadium-containing MXene comprises: adding 1 to 3 parts of lithium fluoride to 10 to 15 parts of a hydrochloric acid solution with a molar concentration of 1 mol / L by weight, stirring for 50 to 60 minutes, and then adding 1 to 3 parts of vanadium aluminum carbide and stirring for 35 to 45 minutes to obtain a mixed solution; stirring the mixed solution at 125 to 130° C. for 50 to 60 hours, washing with deionized water and anhydrous ethanol in sequence, centrifuging, and vacuum drying to obtain the vanadium-containing MXene.

4. The method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution according to claim 1, characterized in that: The preparation method of boron quantum dots comprises: adding 2-4 parts of ammonium pentaborate and 1-2 parts of boric acid to 20-25 parts of deionized water by weight, stirring for 1-2 hours, placing in an argon atmosphere for hydrothermal reaction, cooling to room temperature after the reaction, adding 1-2 parts of hydrazine hydrate, stirring for 1-2 hours, and then centrifuging to obtain a supernatant, and freeze-drying the supernatant to obtain boron quantum dots.

5. The method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution according to claim 4, characterized in that: The reaction temperature of the hydrothermal reaction is 180-185° C., and the reaction time is 10-12 hours.

6. The method for preparing a high-performance nitrogen-containing cemented carbide material based on a vanadium-titanium carbonitride solid solution according to claim 1, characterized in that: The molding agent is selected from any one of paraffin, polyethylene glycol, and polyvinyl alcohol, or a combination of at least two of them.

7. A high-performance nitrogen-containing cemented carbide material based on vanadium-titanium carbonitride solid solution, characterized in that: Prepared according to the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • A high wear-resistant cemented carbide material, its preparation method and application

    CN109811235B

  • Method for preparing carbon-coated high-entropy alloy through photo-reduction method

    CN119140816A